2020
DOI: 10.1515/dmpt-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Using a pharmacogenetic clinical decision support system to improve psychopharmacotherapy dosing in patients with affective disorders

Abstract: ObjectivesAlthough pharmacogenetic tests provide the information on a genotype and the predicted phenotype, these tests do not themselves provide the interpretation of data for a physician. Currently, there are approximately two dozen pharmacogenomic clinical decision support systems (CDSSs) used in psychiatry. Implementation of the CDSSs forming the recommendations on drug and dose selection according to the results of pharmacogenetic testing is an urgent task. Fulfillment of this task will allow increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…One study included a male-only population. 15 Male and female participants each represented approximately half of study populations in 4 articles; 13,14,17,19 female participants were a greater proportion in 2 studies (ranging from 72% to 75.93%) 12,18 and male participants were the greater proportion in the other 2 studies. 11,16…”
Section: Patient Populationmentioning
confidence: 98%
See 4 more Smart Citations
“…One study included a male-only population. 15 Male and female participants each represented approximately half of study populations in 4 articles; 13,14,17,19 female participants were a greater proportion in 2 studies (ranging from 72% to 75.93%) 12,18 and male participants were the greater proportion in the other 2 studies. 11,16…”
Section: Patient Populationmentioning
confidence: 98%
“…Of the potentially relevant articles, 55 publications were excluded for various reasons and 11 publications met the inclusion criteria and were included in this report. These comprised 1 SR, 9 1 HTA, 10 4 RCTs, [11][12][13][14][15] 1 NRS, 16 1 cohort study with historical control, 17 and 2 uncontrolled before-and-after studies. 18,19 Of the RCTs, 2 publications by Ruaño et al reported results from the same trial: 13,14 1 study described the main results 13 and the other summarized findings based on subgroup analyses.…”
Section: Quantity Of Research Availablementioning
confidence: 99%
See 3 more Smart Citations